2006
DOI: 10.1080/13550280600879204
|View full text |Cite
|
Sign up to set email alerts
|

Brain CD8+ and cytotoxic T lymphocytes are associated with, and may be specific for, human immunodeficiency virus type 1 encephalitis in patients with acquired immunodeficiency syndrome

Abstract: CD8+ T cells infiltrate brains with human immunodeficiency virus type-1 (HIV-1) encephalitis (HIVE) and related animal models; their perineuronal localization suggests cytotoxic T cell (CTL)-mediated neuronal killing. Because CTLs have not been identified in acquired immunodeficiency syndrome (AIDS) brains, the authors identified their cytotoxic granules in autopsy AIDS brains with HIVE and without HIVE (HIVnE) plus controls (7 to 13 cases/group) and determined gene expression profiles of CTL-associated genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 67 publications
0
42
1
Order By: Relevance
“…CTLs directly contact with neurons. These are rare or absent in patients who died of HIV disease, but had no evidence of encephalitis, (63). CTL could affect brain injury in HIVE, and as such, could be a biomarker for productive HIV-1 infection in brain in disease.…”
Section: Discussionmentioning
confidence: 99%
“…CTLs directly contact with neurons. These are rare or absent in patients who died of HIV disease, but had no evidence of encephalitis, (63). CTL could affect brain injury in HIVE, and as such, could be a biomarker for productive HIV-1 infection in brain in disease.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that although the major reservoirs for productive infection within the CNS of HIV-1-infected individuals are microglia and monocytes/macrophages, infection of other CNSbased cell types, such as microvascular endothelial cells and neurons, also appears to occur (44,57,92). The role of lymphocytes in AIDS dementia has also been described previously (59,67,68). Of note, viral replication in cerebrospinal fluid is considered to be a marker for the severity of AIDS-related neurodegeneration (16,20).…”
mentioning
confidence: 99%
“…The role of lymphocytes in AIDS dementia has also been described previously (59,67,68). Of note, viral replication in cerebrospinal fluid is considered to be a marker for the severity of AIDS-related neurodegeneration (16,20).…”
mentioning
confidence: 99%
“…CD8+ T cells have been found immediately adjacent to neurons in HIV encephalitis, implicating cytotoxic T cells in neuronal toxicity. 75 Alternatively, an HIV-infected patient with encephalitis after ART has been described with a fulminant focal area…”
Section: Hiv Cns-immune Reconstitution Inflammatory Syndrome Without mentioning
confidence: 99%